Towards Improved Pedagogy in General Studies in Nigerian Universities: University of Agriculture, Makurdi’s Experience - Bola , Adelabu; Ojogbane , Veronica (African Journal of Education,Science and Technology (AJEST), 2014)
Classroom management is commonly cited as one of the greatest problems faced by teachers especially in large classes like General studies classrooms. The learning structure, processes, and environment presently in place in most Nigerian Universities for teaching in General Studies classroom tend to affect adversely learners attitude, interest, motivation and their participation. This study exposed students to a special group work activity. The sample consisted of seven hundred and sixty (760) 200 level students and five hundred and eighty-five (585) 100 level students who registered for GST 222- Peace and Conflict Resolution and GST 116- Communication in English respectively in the second semester of 2011/2012 session. Six research questions were answered through this study. A questionnaire which was designed to elicit information about their perception of the method was administered to the students at the end of the course. The responses showed that the method was worthwhile. Based on the outcome of the study, the researchers postulate that there would be an improvement in students‟ participation in the GST classrooms and academic performance if this method is adopted by the lecturers.